Interação genótipo x ambiente e repetibilidade em palma forrageira no semiárido paraibano - SILVA, BRUNA REGINA DOS SANTOS (2021)
The forage cactus (genus Opuntia and subgenus Nopalea spp.) is the main xerophytic plant cultivated in Brazil, used as a food base for herds, especially in the dry season. Studies aimed at the influence of genotype x environment (GxA) interaction on production traits are extremely important to identify limitations and potentialities of expression of genetic materials. The objective of this work was to study in detail the GxA interaction regarding the productive response of forage cactus cultivars in the semiarid region of Paraíba. This work consists of four chapters. The first one is a literature review. For the others, experiments were carried out in nine Microregions of the Semi-arid Paraibano, totaling sixteen municipalities. Orelha de Elefante Mexicana, Baiana and Miúda, all resistant to Carmine Cochineal, were used. The experimental design was randomized blocks, with four repetitions. The experiments were carried out from 2013 to 2015, regarding the number of cladodes per plant, weight of green mass per plant, average weight of cladodes per plant and dry weight per plant. The data were submitted to univariate analysis of variance together by the environment factor (combination of location and year). For chapters II and III, adaptability and stability analyzes were performed, in addition to graphical analyzes with GGE biplot “Wich won where” (who won where); “Discrimination x Representativeness” “Performance x Stability”; “Ideal Environment” and “Ideal Genotype”. For Chapter IV, a multivariate analysis of variance was performed and the genetic and environmental variance components were estimated by restricted maximum likelihood. From these, the repeatability was estimated. The formation of megaenvironments, repeatable in the two years of evaluation, helped to identify the environments where the genotypes had the highest yields. There was a formation of a single mega-environment for all features. For the number of cladodes per plant and the average weight of the cladodes or megaenvironment, it was composed of the 16 environments and for the weight of green mass per plant and the weight of dry mass per plant, 7 environments. It was possible to observe the potential for possible and representative discrimination of environments within the Microregions. The most adapted and stable genotypes, broadly or specifically, were identified. The selection of the Orelha de Elefante Mexicana genotype is recommended as a superior genetic material for having high performance, being more adapted, stable and generally recommended in the evaluated environments of the semiarid region of Paraíba. For the selection of superior genotypes, the ideal environment is the municipality of Zabelê, as it has a high potential for discrimination and representativeness of the Microregions. In this genotype, the average cladode weight trait has a greater genetic variation than the environmental one, in addition to a high estimate of the repeatability coefficient. The Miúda genotype has specific adaptation in the Princesa Isabel environment, with average repeatability for the cladode number characteristic.